2017
DOI: 10.1186/s41240-017-0073-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of three muscle alpha actin genes in mud loach (Misgurnus mizolepis; Cypriniformes)

Abstract: Background: Teleosts represent unique features in the regulation of muscle development and growth, with a great deal of myogenic plasticity. Muscle actins are major components to compose muscle fibers, and they play essential roles in cellular mobility and other related functions. In order to understand isoform-dependent roles of muscle actins in the mud loach (Misgurnus mizolepis), this study was aimed to characterize gene structure and expression pattern of the three muscle actin isoforms (α-skeletal, α-card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…The findings of this study have also demonstrated that chronic stress down-regulates actin, α cardiac, the primary protein of the thin filament in cardiac sarcomeres, actin α I skeletal muscle a (acta1a) an ATP binding protein in skeletal muscle and cAMP responsive element modulator a (crema). Acta1a activates numerous other “myogenic genes”, which are crucial for the development of muscles [ 70 ]. Crema participates in a number of intracellular activities, including neurogenesis, synaptic potentiation, differentiation, proliferation, and neuroplasticity [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study have also demonstrated that chronic stress down-regulates actin, α cardiac, the primary protein of the thin filament in cardiac sarcomeres, actin α I skeletal muscle a (acta1a) an ATP binding protein in skeletal muscle and cAMP responsive element modulator a (crema). Acta1a activates numerous other “myogenic genes”, which are crucial for the development of muscles [ 70 ]. Crema participates in a number of intracellular activities, including neurogenesis, synaptic potentiation, differentiation, proliferation, and neuroplasticity [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, ACTC1 mutations have been noted in heart diseases, including dilated cardiomyopathy and hypertrophic cardiomyopathy [ 125 , 126 ]. Lee et al observed that ACTC1 is upregulated in mud loaches during the growth stage [ 127 ], and Avey et al suggested that ACTC expression in D. rerio alters the cardiac function and reduces aerobic efficiency [ 128 ]. Further research is warranted to determine whether ACTC mutation and expression during growth influence the growth performance of potato grouper.…”
Section: Discussionmentioning
confidence: 99%
“…ACTC1 encodes Actin Alpha Cardiac Muscle 1 and is classified as highly conserved proteins involved in various types of cell motility [ 71 ]. A lack of ACTC1 may induce apoptosis, which plays a crucial role in embryological development and may also lead to disruption of organ differentiation, specifically defects associated with heart diseases [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%